CREATING AN IQ DEVELOPMENT MOBILE APPLICATION FOR SCHOOL CHILDREN (Web of Teachers: Inderscience Research, 2024)
This study aims to explore fourth-grade students' perceptions of mobile programming education. Data from interviews, metaphors, and drawings were gathered and analyzed qualitatively. Among 135 participants, 24 fourth-graders were purposefully selected. Results indicate positive impacts on students' skills and recommend MIT App Inventor for programming education.